Relative Condition Factor in Nandus nandus (Hamilton) - John, K.C.; Balakrishnan Nair, N. (Fishery Technology, 2025)
The relative condition factor (Kn) was calculated for males and females of Nandus nandus (Hamilton). In males the relative condition factor is above 0.7 in all months and showed two peaks, in August and in October whereas in females it is more or less steady with three median peaks - May, July and September. The results show that there is positive correlation between relative condition factor and reproductive cycle of this fish.